2011
DOI: 10.4161/auto.7.12.18040
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern and functions of autophagy-related geneatg5in zebrafish organogenesis

Abstract: The implications of autophagy-related genes in serious neural degenerative diseases have been well documented. However, the functions and regulation of the family genes in embryonic development remain to be rigorously studied. Here, we report on for the first time the important role of atg5 gene in zebrafish neurogenesis and organogenesis as evidenced by the spatiotemporal expression pattern and functional analysis. Using morpholino oligo knockdown and mRNA overexpression, we demonstrated that zebrafish atg5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 52 publications
4
56
0
Order By: Relevance
“…All 4 transcripts were detected in 1-cell stage-embryos, indicating that they were maternally deposited, as well as at the sphere (3 hpf), germ ring (6 hpf) and 5-somite (12 hpf) stages and at 24 and 48 hpf. atg5 and becn1 transcripts appeared to decrease at the early gastrulation (germ ring) stage, similar to what was reported for atg5, 19 ambra1a, and ambra1b. 20 He and coworkers previously reported that several transcripts including ulk1b are not expressed before 23 hpf.…”
Section: Autophagy Is Active In Early Embryonic Development In Zebrafishsupporting
confidence: 70%
See 3 more Smart Citations
“…All 4 transcripts were detected in 1-cell stage-embryos, indicating that they were maternally deposited, as well as at the sphere (3 hpf), germ ring (6 hpf) and 5-somite (12 hpf) stages and at 24 and 48 hpf. atg5 and becn1 transcripts appeared to decrease at the early gastrulation (germ ring) stage, similar to what was reported for atg5, 19 ambra1a, and ambra1b. 20 He and coworkers previously reported that several transcripts including ulk1b are not expressed before 23 hpf.…”
Section: Autophagy Is Active In Early Embryonic Development In Zebrafishsupporting
confidence: 70%
“…The result is aberrant development of the cardiac chambers and the atrioventricular canal, as well as increased embryonic lethality. While previous studies have indicated that specific autophagy factors are required for development of the Drosophila eye, 12,43 the zebrafish brain, 19,20 and for mouse development (reviewed in ref. 7), our results provide the first evidence that autophagy contributes to the cardiac morphogenic program during vertebrate development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exocytosis and autophagy are essential for a number of common biological processes, including; the immune response (Govind, 2008;Minty et al, 1983;Murray et al, 1998;Ostenson et al, 2006), cell growth (Brennwald & Rossi, 2007;Orlando & Guo, 2009;Wei & Zheng, 2011;Zhang et al, 2005), cell proliferation and apoptosis (Kundu, 2011;Shin et al, 2011;Zeng et al, 2012), and multicellular organism development (Gutnick et al, 2011;Hu et al, 2011;Sato & Sato, 2011;Tra et al, 2011). Autophagy and exocytosis both involve membrane trafficking and fusion events and so similar groups of molecular machinery may be required for both processes: such as GTPase proteins, that facilitate membrane tethering and SNARE proteins which are involved in membrane fusion.…”
Section: Exocytosis and Autophagy: Common Cellular Functions And Molementioning
confidence: 99%